Antagonism of PI 3-kinase-dependent signalling pathways by the tumour suppressor protein, PTEN. (November 2001) - Downes, C. P.; Bennett, D.; McConnachie, G.; Leslie, N. R.; Pass, I.; MacPhee, C.; Patel, L.; Gray, A.
Abstract : The tumour suppressor protein, PTEN (phosphatase and tensin homologue deleted on chromosome 10) is a member of the mixed function, serine/threonine/tyrosine phosphatase subfamily of protein phosphatases. Its physiological substrates, however, are primarily 3-phosphorylated inositol phospholipids, which are products of phosphoinositide 3-kinases. PTEN thus antagonizes PI 3-kinase-dependent signalling pathways, which explains to a large extent its tumour suppressor status. We have examined the kinetic behaviour, substrate specificity and regulation of PTEN both in vitro and in a variety of cellular models. Although PTEN can utilize both phosphatidylinositol 3, 4, 5-trisphosphate [PtdIns-(3, 4, 5)P3 ] and its water-soluble headgroup, inositol 1, 3, 4, 5-tetrakisphosphate, as substrates, it displays classical features of interfacial catalysis, which greatly favour the lipid substrate (by as much as 1000-fold as judged by K cat / K m values). Expression of PTEN in U87 cells (which lack endogenous PTEN) and measuring the levels of all known 3-phosphorylated lipids suggests that phosphatidylinositol 3, 4-bisphosphate and PtdIns(3, 4, 5)P3 are both substrates, but that phosphatidylinositol 3-phosphate and phosphatidyl-inositol 3, 5-bisphosphate are not. PTEN binds to several PDZ-domain-containing proteins via a consensus sequence at its extreme C-terminus. Disruption of targeting to PDZ-domain proteins selectively blocks some PTEN functions, but not others, suggesting the existence of spatially localized, functionally dedicated pools of signalling lipids. We have also shown recently that PTEN expression is controlled at the transcriptional level and is profoundly upregulated by peroxisome proliferator activated receptor γ agonists, thereby providing possible implications for these drugs in diabetes, inflammation and cancer.